2016
DOI: 10.1038/onc.2016.178
|View full text |Cite
|
Sign up to set email alerts
|

Microphthalmia-associated transcription factor suppresses invasion by reducing intracellular GTP pools

Abstract: Melanoma progression is associated with increased invasion and, often, decreased levels of microphthalmia-associated transcription factor (MITF). Accordingly, downregulation of MITF induces invasion in melanoma cells, however little is known about the underlying mechanisms. Here, we report for the first time that depletion of MITF results in elevation of intracellular GTP levels and increased amounts of active (GTP-bound) RAC1, RHO-A and RHO-C. Concomitantly, MITF-depleted cells display larger number of invado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 48 publications
5
33
0
Order By: Relevance
“…Invasion: Recently MITF was shown to control expression of guanosine monophosphate reductase (GMPR) and, consequently, depletion of MITF leads to increased intracellular GTP levels (Bianchi-Smiraglia et al 2017). This is important since increased GTP levels lead to elevated levels of active (GTP-bound) RAC1, RHO-A, and RHO-C, key regulators of the actin cytoskeleton.…”
Section: Mitf Target Genes and Biological Rolementioning
confidence: 99%
“…Invasion: Recently MITF was shown to control expression of guanosine monophosphate reductase (GMPR) and, consequently, depletion of MITF leads to increased intracellular GTP levels (Bianchi-Smiraglia et al 2017). This is important since increased GTP levels lead to elevated levels of active (GTP-bound) RAC1, RHO-A, and RHO-C, key regulators of the actin cytoskeleton.…”
Section: Mitf Target Genes and Biological Rolementioning
confidence: 99%
“…Other evidence suggests that cells exhibiting low MITF expression have greater potential for invasion and that decreasing expression of MITF in vitro promotes greater melanoma invasion [75]. Recently, it was shown that MITF suppresses invasion by reducing intracellular GTP pools by inducing guanosine monophosphate reductase (GMPR); decreased GTP availability results in downregulation of RAC1, RHO-A, and RHO-C [76]. These data have led to a general observation that MITF influences melanoma in a concentration-dependent fashion: high levels of expression are associated with survival and proliferation and low levels of expression with invasion [25].…”
Section: Transcription Factors Of Emtmentioning
confidence: 99%
“…Fibroblasts from aged-tumor bearing mice were found to secrete Wnt-antagnoist sFRP2 which was associated with greater vemurafenib resistance and melanoma metastasis [110]. In vemurafenib resistant melanoma cell lines, loss of MITF downregulated expression of guanosine monophosphate reductase resulting in greater activation of RAC1, RHO-A, and RHO-C; these changes conferred greater invasive potential to resistant cell lines [76]. Another study found that inhibition of BRAF caused activation of NRAS, increased expression of MMP1, urokinase, and other proteases, and ultimately increased melanoma invasion and metastasis in vivo [111].…”
Section: Effects Of Small Molecule Inhibitors On Emt In Melanomamentioning
confidence: 99%
“…In melanoma cells, lineage-specific microphthalmia associated transcription factor (MITF), the master regulator of melanocytic differentiation and development, has also been characterized as a major suppressor of the EMT-like process and invasion (Bianchi-Smiraglia et al, 2016; Carreira et al, 2006b; Hartman and Czyz, 2015; Hoek et al, 2008). Although the MITF gene has been reported to undergo amplification in ~15% of melanomas (Garraway et al, 2005), a significant body of literature demonstrates that strong downregulation of MITF, sometimes even below detection, correlates with poor prognosis and disease progression in patients (Carreira et al, 2006a; Salti et al, 2000; Selzer et al, 2002; Wellbrock and Marais, 2005).…”
Section: Introductionmentioning
confidence: 99%